Evaluation of the antifungal activity of plant extracts and oral antiseptics against Candida albicans - Balliana, Roberta Carvalho Sthel; Jamal, Cláudia Masrouah; Maifrede, Simone Bravim; Araújo, Mariceli Lamas de (Brazilian Dental Science, 2014)
Objective: Oral candidiasis is the most common fungal infection of the oral cavity, and Candida albicans is the most frequently isolated species. Material and Methods: In this study, the potential antifungal effect of extracts from Gossypium hirsutum L., Arctium lappa, Equisetum sp., Cecropia pachystachya Trécul and Pogostemon heyneanus plants were evaluated on non-adhered cells of C. albicans, and the effect of oral antiseptics A (cetylpyridinium chloride 0.500 mg), B (chlorhexidine gluconate 0.12%), C (hydrogen peroxide 1.5%) and D (thymol, eucalyptol, menthol and methyl salicylate) were evaluated on non-adhered cells and biofilms of C. albicans, using turbidimetry and minimal inhibitory concentration (MIC) of the extracts and the maximal inhibitory dilution (MID) of the antiseptics. Results: The most promising results on non-adhered cells were obtained with Cecropia pachystachyaTrécul extracts, with MIC values between 7.81 and 3.91 µg/mL. Antiseptics A and B showed the lowest MID values, between 0.20 and 0.10% (Kruskal-Wallis, p